Sodium-ion battery positive electrode slurry, positive electrode plate, preparation method of positive electrode plate and sodium-ion battery

By using a composite dispersant of polyacrylic acid and its derivatives and polyoxyethylene ether in the sodium ion battery positive electrode slurry, the problem of poor dispersion of polyanionic materials in the sodium ion battery positive electrode slurry is solved, and lower resistance and better cycle performance are achieved.

CN119560504AActive Publication Date: 2025-03-04XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411647443.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-04
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Polyanionic materials have problems such as large resistance, high proportionality, small particle size and high moisture in the positive electrode slurry of sodium ion batteries, resulting in poor dispersion and high resistance, which affects the cycling performance and safety of the battery.

Method used

The ionic dispersant of polyacrylic acid and its derivatives is used in combination with the polyoxyethylene ether non-ionic dispersant to form a composite dispersant, and the composite is formed through mechanical mixing or chemical reactions, which is used to improve the dispersion and stability of the positive electrode slurry.

Benefits of technology

The dispersion and stability of the positive electrode slurry are improved, the resistance of the positive electrode sheet is reduced, and the circulation performance and safety of the sodium ion battery are optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560504A_ABST
    Figure CN119560504A_ABST
Patent Text Reader

Abstract

The invention provides sodium-ion battery positive electrode slurry, a positive electrode plate, a preparation method of the positive electrode plate and a sodium-ion battery, and relates to the technical field of sodium-ion batteries, the sodium-ion battery positive electrode slurry comprises a positive electrode active material, a conductive agent, a binder, a composite dispersant and a solvent; the composite dispersing agent is a product formed by mechanically mixing an ionic dispersing agent and a polyoxyethylene ether nonionic dispersing agent or a compound formed by chemically reacting the ionic dispersing agent and the polyoxyethylene ether nonionic dispersing agent, and the ionic dispersing agent is polyacrylic acid and a derivative thereof; and the positive electrode active material is a polyanion material. According to the positive electrode slurry disclosed by the invention, the ionic dispersant of polyacrylic acid and a derivative thereof and the polyoxyethylene ether nonionic dispersant are compounded for use, so that the positive electrode slurry has good dispersity and stability, the provided positive electrode slurry is good in dispersity, the resistance of a positive electrode plate is low, and the cycle performance of the sodium ion battery is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode slurry, a positive electrode sheet and a preparation method thereof, and a sodium ion battery. Background Art

[0002] In the context of the rapid development of new energy technologies around the world, sodium-ion batteries (SIBs) are widely considered to be one of the ideal choices for future large-scale energy storage systems due to their abundant resources, low cost, and environmental friendliness. However, the performance of sodium-ion batteries is limited by the selection and optimization of cathode materials. At present, layered oxides, Prussian blue, and polyanion materials are considered to be the most promising cathode materials.

[0003] Polyanion materials have become a hot topic in the research of positive electrode materials for sodium ion batteries due to their high operating voltage, open and stable structure, and excellent structural and thermal stability. However, these materials generally have the characteristics of high resistance, high specific surface area, small particle size, and high water content, which leads to interactions between active material particles in the positive electrode slurry system, forming larger agglomerates, failing to achieve an ideal dispersion state and forming a uniform conductive path; at the same time, the viscosity stability of the positive electrode slurry deteriorates, resulting in poor consistency in coating surface density and electrode sheet resistance, which will reduce the service life and safety of the battery. Therefore, there is an urgent need to rationally design the positive electrode slurry, improve the dispersibility and stability of the polyanion material, reduce the electrode sheet resistance, and optimize the cycle performance of sodium ion batteries. Summary of the invention

[0004] The object of the present invention is to provide a positive electrode slurry for a sodium ion battery, a positive electrode sheet and a preparation method thereof, and a sodium ion battery. The positive electrode slurry uses a composite of an ionic dispersant of polyacrylic acid and its derivatives and a polyoxyethylene ether nonionic dispersant, especially a product obtained by polymerization of polyacrylic acid maleic anhydride or polyacrylic acid maleic acid ionic dispersant and bisphenol A polyoxyethylene ether nonionic dispersant as a composite dispersant, and is combined with other raw materials to make the positive electrode slurry have good dispersibility and stability. The positive electrode slurry provided by the present invention has good dispersibility, low positive electrode sheet resistance, and excellent cycle performance of the sodium ion battery.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect of the present invention, a positive electrode slurry for a sodium ion battery is provided, comprising: a positive electrode active material, a conductive agent, a binder, a composite dispersant and a solvent;

[0007] The composite dispersant is a product formed by mechanically mixing an ionic dispersant with a polyoxyethylene ether nonionic dispersant, or a complex formed by chemically reacting an ionic dispersant with a polyoxyethylene ether nonionic dispersant, wherein the ionic dispersant is polyacrylic acid and its derivatives;

[0008] The positive electrode active material is a polyanion material.

[0009] Furthermore, the mass of the composite dispersant accounts for 0.2%-1.0% of the total mass of the positive electrode active material, the conductive agent, the binder and the composite dispersant;

[0010] And / or, the ionic dispersant is a copolymer formed by polyacrylic acid and other polycarboxylic acids or anhydrides;

[0011] And / or, the polyoxyethylene ether nonionic dispersant is alcohol polyoxyethylene ether or phenol polyoxyethylene ether;

[0012] and / or, in the composite formed after the chemical reaction between the ionic dispersant and the polyoxyethylene ether nonionic dispersant, the chemical reaction refers to an esterification reaction between the carboxyl group in the ionic dispersant and the hydroxyl group in the nonionic dispersant to form an ester bond;

[0013] And / or, in the preparation of the composite dispersant, the mass ratio of the ionic dispersant to the polyoxyethylene ether nonionic dispersant is (1-2): (2-5);

[0014] and / or, in the positive electrode slurry, the mass ratio of the positive electrode active material, the conductive agent, the binder and the composite dispersant is (93-97): (1-2): (1-4): (0.2-1.0), and the sum of the mass ratios is 100;

[0015] And / or, the solid content of the positive electrode slurry is 55%-65%;

[0016] And / or, the viscosity of the positive electrode slurry is 3000-12000 mPa·S.

[0017] Further, the ionic dispersant is polyacrylic acid maleic anhydride or polyacrylic acid maleic acid;

[0018] And / or, the polyoxyethylene ether nonionic dispersant is one or more of bisphenol A polyoxyethylene ether, glycerol polyoxyethylene ether, furan methanol polyoxyethylene ether, nonylphenol polyoxyethylene ether, and 1,2-propylene glycol polyoxypropylene polyoxyethylene ether;

[0019] and / or, the positive electrode active material is selected from at least one of sodium ferric pyrophosphate, sodium ferrous sulfate, sodium vanadium phosphate, and sodium ferric phosphate;

[0020] and / or, the conductive agent is selected from at least one of carbon black, graphene, carbon nanotubes or carbon nanofibers;

[0021] And / or, the binder is selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene or PFA emulsion;

[0022] and / or, the solvent is selected from at least one of N-methylpyrrolidone, ethanol, isopropanol or acetone;

[0023] And / or, the composite dispersant is prepared according to the following method: deionized water is added to a mixture of an ionic dispersant and a polyoxyethylene ether non-ionic dispersant to form a gel solution, and then the mixture is stirred and reacted at 140-160° C. for 4-8 hours under vacuum conditions with a catalyst; and the reaction product is then post-treated to obtain the composite dispersant.

[0024] Furthermore, the composite dispersant is a composite formed by a chemical reaction between polyacrylic acid maleic anhydride or polyacrylic acid maleic acid and bisphenol A polyoxyethylene ether.

[0025] Furthermore, the preparation method of the composite obtained by chemical reaction of polyacrylic acid maleic anhydride or polyacrylic acid maleic acid with bisphenol A polyoxyethylene ether comprises the following steps:

[0026] S1: adding polyacrylic acid maleic anhydride or polyacrylic acid maleic acid and bisphenol A polyoxyethylene ether in a mass ratio of (1-2): (2-5) into a reaction kettle, and then adding deionized water to form a glue solution, stirring and reacting at 140-160° C. under vacuum conditions for 4-8 hours under the action of a catalyst;

[0027] S2: After the reaction is completed, sodium carbonate solution is added to the reactor of step S1 and stirred, and then the solid product is washed with saturated brine, and then the washed solid product is dissolved in ethyl acetate, and finally the obtained liquid is vacuum dried to remove the ethyl acetate solvent, so as to obtain a composite.

[0028] Furthermore, the solid content of the glue solution is 8-12%;

[0029] And / or, the vacuum condition is evacuated to 0.05-1.0Kpa;

[0030] And / or, the catalyst is p-toluenesulfonic acid, and its addition amount accounts for 0.6-1% of the total mass of the two reaction raw materials;

[0031] And / or, the mass concentration of the sodium carbonate solution is 8-12%, and the amount of the sodium carbonate added is such that the added sodium carbonate is 1 / 5 to 1 / 3 of the mass of the added catalyst;

[0032] And / or, the stirring time in step S2 is 25-35 min.

[0033] The second aspect of the present invention provides a method for preparing the positive electrode slurry for a sodium ion battery according to the first aspect, comprising the following steps:

[0034] The binder, composite dispersant and solvent are mixed and stirred, and then a conductive agent is added for sizing, and then the positive electrode active material is added for homogenization, and then an appropriate amount of solvent is added to adjust the solid content and viscosity of the slurry to obtain a positive electrode slurry.

[0035] Furthermore, when the binder, the composite dispersant and the solvent are mixed and stirred, the amount of the solvent added is controlled so that the solid content of the slurry reaches 5%-8%, and the stirring time is 120-180 minutes;

[0036] The mixing time of the glue application is 90-150min;

[0037] The homogenization time is 120-180 min.

[0038] The third aspect of the present invention provides a positive electrode plate, including a current collector and a positive electrode active layer coated on the surface of the current collector, wherein the positive electrode active layer is made of the positive electrode slurry described in the first aspect of the present invention or the positive electrode slurry prepared by the preparation method described in the second aspect of the present invention.

[0039] A fourth aspect of the present invention provides a sodium ion battery, comprising the positive electrode sheet described in the third aspect.

[0040] The technical solution provided by the present invention has the following beneficial effects:

[0041] Polyacrylic acid and its derivative ionic dispersants contain abundant carboxyl structures, which can be adsorbed on the surface of positive electrode particles, reduce the surface energy of particles, and repel surrounding particles through the charge on the surface of particles. After adsorption, they have a steric effect to prevent particles from approaching, producing a composite stabilizing effect. In order to increase the number of carboxyl groups and improve the effect, the ionic dispersant is a copolymer formed by polyacrylic acid and other polycarboxylic acids or anhydrides.

[0042] When polyacrylic acid maleic anhydride is selected as the ionic dispersant, maleic anhydride will form maleic acid when it meets water. Therefore, this dispersant can reduce the impact of the water content of the material on the sodium ion battery.

[0043] Polyoxyethylene ether contains -OH, which can be well adsorbed on the surface of the positive electrode material and the conductive agent to form hydrogen bonds. For the conductive agent with a large specific surface area, in order to improve the adsorption effect of the dispersant on it, the polyoxyethylene ether dispersant is preferably selected as a phenolic non-ionic dispersant such as bisphenol A polyoxyethylene ether, which can also be effectively adsorbed on the surface of the conductive agent through the π-π bond of the benzene ring and the short-chain alkane structure. The free long chain The structure produces a steric hindrance effect to prevent the entanglement and agglomeration of the conductive agent.

[0044] The present invention more preferably further polymerizes the polypropylene maleic anhydride ionic dispersant and the bisphenol A polyoxyethylene ether nonionic dispersant to form a composite dispersant, which has the advantages of both the polypropylene maleic anhydride ionic dispersant and the bisphenol A polyoxyethylene ether nonionic dispersant. It can utilize the ortho-carboxyl structure to enhance the electronegativity of the surface of the positive electrode particles, and prevent the particles from agglomerating through the electrostatic repulsion mechanism. At the same time, it utilizes a large number of -OH hydroxyl groups and benzene rings to anchor the particles and the conductive agent, and combines with the solvated long chain to achieve a dispersion effect through a steric hindrance mechanism, which can not only make the positive electrode material and the conductive agent well dispersed, but also promote the conductive agent to be evenly dispersed on the surface of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Schematic diagram of the dispersant adsorbed on the surface of the positive electrode active material. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0047] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0048] According to a first aspect of the present invention, the present invention provides a positive electrode slurry for a sodium ion battery comprising: a positive electrode active material, a conductive agent, a binder, a composite dispersant and a solvent;

[0049] The composite dispersant is a product formed by mechanically mixing an ionic dispersant with a polyoxyethylene ether nonionic dispersant, or a complex formed by chemically reacting an ionic dispersant with a polyoxyethylene ether nonionic dispersant, wherein the ionic dispersant is polyacrylic acid and its derivatives;

[0050] The positive electrode active material is a polyanion material.

[0051] Polyacrylic acid and its derivative ionic dispersants contain abundant carboxyl structures, which can be adsorbed on the surface of positive electrode particles, reduce the surface energy of particles, and repel surrounding particles through the charge on the surface of particles. After adsorption, they have a steric effect to prevent particles from approaching, thus producing a composite stabilizing effect. In order to increase the number of carboxyl groups and improve the effect, the ionic dispersant is a copolymer formed by polyacrylic acid and other polycarboxylic acids or anhydrides. For example: polyacrylic acid maleic anhydride, polyacrylic acid maleic acid, polyacrylic acid itaconic acid, carboxylic acid-sulfonic acid-acrylate terpolymer.

[0052] The polyoxyethylene ether nonionic dispersant is adsorbed on the surface of the positive electrode material and the conductive agent through the hydroxyl group, and the free long-chain structure produces a steric hindrance effect to achieve a good dispersion effect.

[0053] In order to improve the dispersion effect, the polyoxyethylene ether nonionic dispersant is alcohol polyoxyethylene ether or phenol polyoxyethylene ether; preferably one or more of bisphenol A polyoxyethylene ether, glycerol polyoxyethylene ether, furan methanol polyoxyethylene ether, nonylphenol polyoxyethylene ether, and 1,2-propylene glycol polyoxypropylene polyoxyethylene ether;

[0054] Alcohol polyoxyethylene ether or phenol polyoxyethylene ether contains -OH, which can be well adsorbed on the surface of the positive electrode material and the conductive agent to form hydrogen bonds. However, compared with the positive electrode material (micrometer level), the particle size of the conductive agent is nanometer level (less than 40 nanometers) and has a large specific surface area. The adsorption effect is usually limited only through -OH adsorption. For example, glycerol polyoxyethylene ether, furan methanol polyoxyethylene ether, and 1,2-propylene glycol polyoxypropylene polyoxyethylene ether can be adsorbed on the surface of the conductive agent, but because the conductive agent is a nano-sized material (the positive electrode material is micrometer level), its effect is limited. Phenolic non-ionic dispersants such as bisphenol A polyoxyethylene ether can also be effectively adsorbed on the surface of the conductive agent through the π-π bond of the benzene ring and the short-chain alkane structure. The free long-chain The structure produces a steric hindrance effect to prevent the entanglement and agglomeration of the conductive agent; therefore, the polyoxyethylene ether nonionic dispersant is preferably bisphenol A polyoxyethylene ether or nonylphenol polyoxyethylene ether.

[0055] The composite dispersant can be a product formed by mechanical and physical mixing of an ionic dispersant and a polyoxyethylene ether nonionic dispersant, or a complex formed by a chemical reaction between the ionic dispersant and the polyoxyethylene ether nonionic dispersant, wherein the chemical reaction refers to an esterification reaction between the carboxyl group in the ionic dispersant and the hydroxyl group in the nonionic dispersant to form an ester bond.

[0056] It should be noted that the product formed by mechanically mixing the ionic dispersant and the polyoxyethylene ether non-ionic dispersant is a product obtained by mechanically stirring and mixing the two. The product also contains crosslinks caused by the esterification reaction, but the final form and molecular weight of the product are difficult to control. The product formed after mechanical mixing is not as good as the dispersion effect of the complex formed by the regular chemical reaction under the conditions of catalyst and heating, and the stability of the slurry processing technology will be affected. Therefore, the complex is better than the product of simple mechanical mixing.

[0057] In the composite dispersant, in order to improve the synergistic effect of the two dispersants, the mass ratio of the ionic dispersant to the polyoxyethylene ether nonionic dispersant is (1-2): (2-5) (e.g., 1:3, 1:4, 1.5:2, 1.5:3, 1.5:4, 2:3, 2:4);

[0058] If the mass ratio of the ionic dispersant to the polyoxyethylene ether nonionic dispersant is higher than (1-2): (2-5), there will be too much ionic dispersant and too little nonionic dispersant, which can play a certain dispersing role on the positive electrode material, but the dispersion of the conductive agent is affected and the positive electrode sheet resistance is large; if the ratio is lower than this, there will be too little ionic dispersant and too much nonionic dispersant, long chain entanglement will occur and the slurry viscosity will be unstable.

[0059] The composite formed by the chemical reaction between the ionic dispersant and the polyoxyethylene ether nonionic dispersant is prepared according to the following method: deionized water is added to the mixture of the ionic dispersant and the polyoxyethylene ether nonionic dispersant to form a gel solution, and then the mixture is stirred and reacted at 140-160°C (such as 145°C, 150°C, 155°C, etc.) under vacuum conditions for 4-8h (such as 4.5h, 5.5h, 6.5h, 7.5h) under the action of a catalyst; and then the reaction product is post-treated to obtain the composite dispersant. The post-treatment includes purification and refining processes.

[0060] As a preferred embodiment, the composite dispersant is a composite formed by a chemical reaction between polyacrylic acid maleic anhydride or polyacrylic acid maleic acid and bisphenol A polyoxyethylene ether.

[0061] Polypropylene maleic anhydride ionic dispersant reacts with trace water in the slurry to generate polypropylene maleic acid, which contains rich carboxyl structures and can be adsorbed on the surface of positive electrode particles to reduce the surface energy of the particles. It also repels surrounding particles through the charge on the surface of the particles. After adsorption, it has a steric effect to prevent particles from approaching, producing a composite stabilizing effect. For details, see Figure 1 . Polypropylene maleic anhydride can reduce the impact of material water content on sodium ion batteries.

[0062] Bisphenol A polyoxyethylene ether nonionic dispersant effectively adsorbs on the surface of the conductive agent through the π-π bond of the benzene ring and the short-chain alkane structure, and the free long chain The structure produces a steric hindrance effect to prevent the entanglement and agglomeration of the conductive agent.

[0063] Polypropylene maleic anhydride ionic dispersant and bisphenol A polyoxyethylene ether non-ionic dispersant can be further polymerized to form a composite dispersant, which utilizes the ortho-carboxyl structure to enhance the surface electronegativity of the positive electrode particles, prevents particle agglomeration through the electrostatic repulsion mechanism, and simultaneously utilizes a large number of -OH hydroxyl groups and benzene rings to anchor the particles and the conductive agent, combined with the solvated long chain, to achieve a dispersion effect through a steric hindrance mechanism, which can not only achieve good dispersion of the positive electrode material and the conductive agent, but also promote the conductive agent to be evenly dispersed on the surface of the positive electrode material.

[0064] The positive electrode active material is selected from at least one of sodium ferric pyrophosphate, sodium ferrous sulfate, sodium vanadium phosphate, and sodium ferric phosphate;

[0065] The conductive agent may be a conductive agent of a conventional sodium ion battery. Typically, but not limitedly, the conductive agent is selected from at least one of carbon black, graphene, carbon nanotubes or carbon nanofibers;

[0066] The binder may be a binder of a conventional sodium ion battery. Typically, but not limitedly, the binder is selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene or PFA emulsion;

[0067] The solvent may be a solvent used in a conventional sodium ion battery positive electrode. Typically, but not limiting, the solvent is selected from at least one of N-methylpyrrolidone, ethanol, isopropanol or acetone.

[0068] The dosage of the composite dispersant can be the dosage of a conventional dispersant, but in order to further ensure the dispersion effect, the mass of the composite dispersant accounts for 0.1-1.8% (such as 0.2%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%) of the total mass of the positive electrode active material, conductive agent, binder and composite dispersant, preferably 0.2%-1.0%.

[0069] If the amount of the composite dispersant is too small, the dispersing effect cannot be achieved. If the amount of the dispersant is too large, long chain entanglement will occur, reducing the dispersing effect.

[0070] The amounts of the positive electrode active material, the conductive agent, and the binder are all conventional amounts in the art. In the positive electrode slurry, the mass ratio of the positive electrode active material, the conductive agent, the binder, and the composite dispersant is preferably (93-97): (1-2): (1-4): (0.2-1.0), and the sum of the mass ratios is 100;

[0071] The solid content of the positive electrode slurry may be a conventional solid content, typically but not limited to 55%-65%;

[0072] The viscosity of the positive electrode slurry may be a conventional viscosity, typically but not limited to 3000-12000 mPa·S.

[0073] The preparation method of the composite obtained by chemical reaction of polyacrylic acid maleic anhydride or polyacrylic acid maleic acid and bisphenol A polyoxyethylene ether comprises the following steps:

[0074] S1: adding polyacrylic acid maleic anhydride or polyacrylic acid maleic acid and bisphenol A polyoxyethylene ether in a mass ratio of (1-2): (2-5) into a reaction kettle, and then adding deionized water to form a glue solution, stirring and reacting at 140-160° C. under vacuum conditions for 4-8 hours under the action of a catalyst;

[0075] S2: After the reaction is completed, sodium carbonate solution is added to the reactor of step S1 and stirred, and then the solid product is washed with saturated brine, and then the washed solid product is dissolved in ethyl acetate, and finally the obtained liquid is vacuum dried to remove the ethyl acetate solvent, so as to obtain a composite.

[0076] Furthermore, the solid content of the glue solution is 8-12%, preferably 10%;

[0077] Furthermore, the vacuum condition is evacuated to 0.05-1.0Kpa;

[0078] Furthermore, the catalyst is p-toluenesulfonic acid, and its addition amount accounts for 0.6-1% of the total mass of the two reaction raw materials, preferably 0.8%;

[0079] Furthermore, the mass concentration of the sodium carbonate solution is 8-12%, preferably 10%, and the amount of the sodium carbonate added is such that the added sodium carbonate is 1 / 5 to 1 / 3, preferably 1 / 4 of the mass of the added catalyst;

[0080] Furthermore, the stirring time in step S2 is 30 min.

[0081] Specifically, the preparation method of the composite dispersant comprises the following steps:

[0082] (1) Adding polyacrylic acid maleic anhydride or polypropylene maleic acid and bisphenol A polyoxyethylene ether in a mass ratio of (1-2): (2-5) into a reaction kettle, adding deionized water to form a glue solution with a solid content of 10%, adding a catalyst, evacuating to 0.05-1.0Kpa (for example, 0.1Kpa, 0.2Kpa, 0.3Kpa, 0.4Kpa, 0.5Kpa, 0.6Kpa, 0.7Kpa, 0.8Kpa, 0.9Kpa), heating to 140-160°C (for example, 145°C, 150°C, 155°C), stirring and reacting for 4-8h (for example, 5h, 6h, 7h); the catalyst is p-toluenesulfonic acid, and its addition amount accounts for 0.8% of the total mass of the reactants.

[0083] (2) adding a sodium carbonate solution with a mass concentration of 10% into a reaction kettle, wherein the amount of sodium carbonate added is 1 / 4 of the amount of toluenesulfonic acid added, stirring and reacting for 30 minutes, washing the product with saturated brine, and separating the solid and liquid to obtain a solid mixture; dissolving the solid mixture in ethyl acetate, and vacuum drying the obtained liquid to obtain a composite dispersant.

[0084] The specific reactions are as follows:

[0085]

[0086] The above reaction formula only schematically shows one of the reaction sites of the two dispersants. In the actual reaction, maleic anhydride may also undergo esterification reaction with the terminal hydroxyl group of bisphenol A polyoxyethylene ether after being decomposed into maleic acid by water.

[0087] The purpose of washing the product with saturated brine in the above step is to wash away sodium carbonate and sodium p-toluenesulfonate; after the solid mixture is dissolved in ethyl acetate, solid-liquid separation can be achieved to remove sodium chloride.

[0088] According to a second aspect of the present invention, the present invention provides a method for preparing a positive electrode slurry for a sodium ion battery, comprising the following steps:

[0089] The binder, composite dispersant and solvent are mixed and stirred, and then a conductive agent is added for sizing, and then the positive electrode active material is added for homogenization, and then an appropriate amount of solvent is added to adjust the solid content and viscosity of the slurry to obtain a positive electrode slurry.

[0090] Specifically, a binder, a composite dispersant and a solvent are added to a container and mixed and stirred, the amount of solvent added is controlled so that the solid content of the slurry reaches 5%-8% (for example, 6%, 7%), and stirred for 120-180 minutes (for example, 130 minutes, 140 minutes, 150 minutes, 160 minutes, 170 minutes), and then a conductive agent is added for glueing, stirred for 90-150 minutes (for example, 100 minutes, 110 minutes, 120 minutes, 130 minutes, 140 minutes), and then the positive electrode active material is added for 120-180 minutes (for example, 130 minutes, 140 minutes, 150 minutes, 160 minutes, 170 minutes), and an appropriate amount of solvent is added to adjust the solid content and viscosity of the slurry to obtain a positive electrode slurry;

[0091] The positive electrode active material includes at least one of polyanion materials such as sodium ferric pyrophosphate, sodium ferrous sulfate, sodium vanadium phosphate, and sodium ferric phosphate;

[0092] The conductive agent includes at least one of carbon black, graphene, carbon nanotubes or carbon nanofibers;

[0093] The binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) or soluble polytetrafluoroethylene (PFA) emulsion;

[0094] The solvent includes at least one of N-methylpyrrolidone, ethanol, isopropanol or acetone.

[0095] As an optional embodiment of the method for preparing the positive electrode slurry of a sodium ion battery of the present invention, the solid content of the positive electrode slurry is 55%-65% (e.g., 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%);

[0096] And / or, the viscosity of the positive electrode slurry is 3000-12000 mPa·S (for example, 4000 mPa·S, 5000 mPa·S, 6000 mPa·S, 7000 mPa·S, 8000 mPa·S, 9000 mPa·S, 10000 mPa·S, 11000 mPa·S,).

[0097] According to a third aspect of the present invention, the present invention provides a positive electrode plate, comprising a current collector and a positive electrode active layer coated on the surface of the current collector, wherein the positive electrode active layer is made of the above-mentioned positive electrode slurry or the positive electrode slurry prepared by the above-mentioned preparation method.

[0098] According to a fourth aspect of the present invention, the present invention provides a sodium ion battery comprising the above-mentioned positive electrode plate.

[0099] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0100] The dispersants used in the following examples and comparative examples are derived from:

[0101] Polyacrylic acid maleic anhydride was purchased from Hubei Shishun Biotechnology Co., Ltd., CAS number 26677-99-6;

[0102] Bisphenol A polyoxyethylene ether was purchased from Hubei Qifei Pharmaceutical Chemical Co., Ltd., CAS number 32492-61-8;

[0103] Glycerol polyoxyethylene ether was purchased from Shandong Haizhou Bioengineering Co., Ltd., CAS number 31694-55-0;

[0104] Polyacrylic acid was purchased from Hubei Shixing Chemical Co., Ltd., CAS number 9007-20-9;

[0105] Nonylphenol polyoxyethylene ether was purchased from Shanghai Jieshikai Biotechnology Co., Ltd., CAS number 127087-87-0;

[0106] 1,2-Propanediol polyoxypropylene ether was purchased from Hai'an Petrochemical Plant in Jiangsu Province with a CAS number of 53637-25-5.

[0107] Example 1

[0108] This embodiment provides a positive electrode slurry, including the following raw materials: positive electrode active material, conductive agent, binder, composite dispersant and solvent. Among them, the positive electrode active material is sodium ferric pyrophosphate, the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (PVDF), the composite dispersant is polyacrylic acid maleic anhydride-bisphenol A polyoxyethylene ether composite dispersant, and the solvent is N-methylpyrrolidone (NMP). The mass ratio of positive electrode active material, conductive agent, binder and composite dispersant is 94.4:2.0:3.0:0.6. The amount of solvent added must ensure that the solid content is 61%.

[0109] The method for preparing the positive electrode slurry provided in this embodiment comprises the following steps:

[0110] (a) Add polyacrylic acid maleic anhydride and bisphenol A polyoxyethylene ether in a mass ratio of 1:3 into a reaction kettle, add deionized water to form a glue solution with a solid content of 10%, add catalyst p-toluenesulfonic acid (0.8% of the total mass of the two raw materials), evacuate to 0.05-1.0Kpa, heat to 150°C, and stir to react for 6 hours.

[0111] (b) adding a sodium carbonate solution with a mass concentration of 10% to a reaction kettle, wherein the amount of sodium carbonate added is 1 / 4 of the amount of toluenesulfonic acid added, stirring and reacting for 30 minutes, washing the product with saturated brine to remove sodium carbonate and sodium p-toluenesulfonate, and separating the solid and liquid to obtain a solid mixture. Dissolving the solid mixture in ethyl acetate, separating the solid and liquid to remove sodium chloride, and vacuum drying the liquid to obtain a composite dispersant.

[0112] (c) According to the ratio of each substance in the positive electrode slurry, the binder PVDF, part of the solvent NMP and the composite dispersant obtained in step (b) are added to the container, and the amount of NMP added is controlled so that the solid content of the slurry reaches 5%-8%. Stir for 120 minutes, then add the conductive agent SP and stir for 150 minutes, add the positive electrode active material sodium ferric pyrophosphate and slurry for 180 minutes, add an appropriate amount of solvent NMP to adjust the slurry viscosity to 5100mPa·S, and obtain a positive electrode slurry with a solid content of 61%.

[0113] Example 2

[0114] This embodiment provides a positive electrode slurry, including the following raw materials: positive electrode active material, conductive agent, binder, composite dispersant and solvent. Among them, the positive electrode active material is sodium ferric pyrophosphate, the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (PVDF), the composite dispersant is a mixture of polyacrylic acid maleic anhydride ionic dispersant and bisphenol A polyoxyethylene ether non-ionic dispersant, and the solvent is N-methylpyrrolidone (NMP). The mass ratio of positive electrode active material, conductive agent, binder and composite dispersant is 94.4:2.0:3.0:0.6. The amount of solvent added must ensure that the solid content is 60%.

[0115] The method for preparing the positive electrode slurry provided in this embodiment comprises the following steps:

[0116] (a) Polyacrylic acid maleic anhydride and bisphenol A polyoxyethylene ether are mechanically mixed in a mass ratio of 1:3 to obtain a composite dispersant.

[0117] (b) According to the ratio of each material in the positive electrode slurry, the binder PVDF, part of the solvent NMP and the composite dispersant obtained in step (a) are added to the container, and the amount of NMP added is controlled so that the solid content of the slurry reaches 6%. Stir for 120 minutes, add the conductive agent SP and stir for 150 minutes, add the positive electrode active material sodium ferric pyrophosphate and slurry for 180 minutes, add an appropriate amount of solvent NMP to adjust the slurry viscosity to 5200mPa·S, and obtain a positive electrode slurry with a solid content of 60%.

[0118] Example 3

[0119] This embodiment provides a positive electrode slurry. Compared with Example 1, except that the polyacrylic acid maleic anhydride-bisphenol A polyoxyethylene ether composite dispersant is replaced by polyacrylic acid maleic anhydride-glycerol polyoxyethylene ether composite dispersant, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0120] Example 4

[0121] This embodiment provides a positive electrode slurry. Compared with Example 1, except that the mass ratio of the positive electrode active material, the conductive agent, the binder and the composite dispersant is replaced from 94.4:2.0:3.0:0.6 to 94:2.0:3.0:1.0, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0122] Example 5

[0123] This embodiment provides a positive electrode slurry. Compared with Example 1, except that the mass ratio of the positive electrode active material, the conductive agent, the binder and the composite dispersant is replaced by 94.8:2.0:3.0:0.2, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0124] Example 6

[0125] This embodiment provides a positive electrode slurry. Compared with Example 1, except that the polyacrylic acid maleic anhydride-bisphenol A polyoxyethylene ether composite dispersant is replaced by polyacrylic acid-bisphenol A polyoxyethylene ether composite dispersant, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0126] Example 7

[0127] This embodiment provides a positive electrode slurry. Compared with Example 1, except that the polyacrylic acid maleic anhydride-bisphenol A polyoxyethylene ether composite dispersant is replaced by polyacrylic acid maleic anhydride-nonylphenol polyoxyethylene ether composite dispersant, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0128] Example 8

[0129] This embodiment provides a positive electrode slurry. Compared with Example 1, except that the polyacrylic acid maleic anhydride-bisphenol A polyoxyethylene ether composite dispersant is replaced by polyacrylic acid maleic anhydride-1,2-propylene glycol polyoxypropylene polyoxyethylene ether composite dispersant, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0130] Comparative Example 1

[0131] This comparative example provides a positive electrode slurry. Compared with Example 1, except that the mass ratio of the positive electrode active material, the conductive agent, the binder and the composite dispersant is replaced by 95:2.0:3.0:0.0, that is, the addition amount of the composite dispersant is adjusted to 0%, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0132] Comparative Example 2

[0133] This comparative example provides a positive electrode slurry. Compared with Example 1, except that the mass ratio of the positive electrode active material, the conductive agent, the binder and the composite dispersant is replaced by 93.0:2.0:3.0:2.0, that is, the addition amount of the composite dispersant is adjusted to 2.0%, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0134] Comparative Example 3

[0135] This comparative example provides a positive electrode slurry. Except that the polypropylene maleic anhydride-bisphenol A polyoxyethylene ether composite dispersant is replaced by a polyacrylic acid maleic anhydride ionic dispersant, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0136] Comparative Example 4

[0137] This comparative example provides a positive electrode slurry. Except that the polypropylene maleic anhydride-bisphenol A polyoxyethylene ether composite dispersant is replaced by a bisphenol A polyoxyethylene ether non-ionic dispersant, the other raw material types, amounts and preparation methods are the same as those in Example 1.

[0138] Performance Testing

[0139] Assembly and performance testing of sodium ion batteries:

[0140] Preparation of positive electrode sheets: The positive electrode slurries in Examples 1-8 and Comparative Examples 1-4 were used to prepare positive electrode sheets, and the positive electrode slurries were evenly coated on aluminum foil, with a single-sided coating density of 150 g / m 2 After baking and rolling, the positive electrode sheet is obtained. The thickness of the aluminum foil is 14 μm and the compaction density is 2.0 g / cm 3 .

[0141] Preparation of negative electrode sheets: When hard carbon materials are used as active materials and different positive electrode sheets are used to assemble sodium-ion batteries, the negative electrode sheets used are prepared by the same method and batch.

[0142] Preparation of sodium ion battery: The above positive electrode sheets are assembled with the negative electrode sheets into battery cells, and the soft-pack lamination process is used to make soft-pack sodium ion batteries. The sodium iron pyrophosphate positive electrode sheet, the hard carbon negative electrode sheet and the polyethylene diaphragm (for example: PE+OBS diaphragm) are stacked and assembled, and then baked until the moisture content is qualified, and the electrolyte is injected. After hot pressing and high-temperature standing, it is packaged, and after volume separation, it is stood at room temperature to obtain a soft-pack finished battery with a theoretical capacity of 5Ah.

[0143] Among them, the electrolyte solvents are ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), the sodium salts are NaPF6 and NaFSI, and the additives are vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfate (DTD) and 1,3-propane sultone (1-3PS).

[0144] The electrolyte uses a conventional electrolyte in the art, and the solvents it contains are ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), wherein the mass ratio of EC:PC:EMC:DMC is about 20:10:50:20, the sodium salts it contains are sodium hexafluorophosphate (NaPF6, with a concentration of about 14 weight %) and sodium bis(fluorosulfonyl)imide (NaFSI, with a concentration of about 3 weight %), and the additives it contains are vinylene carbonate (VC, with a concentration of about 0.8 weight %), fluoroethylene carbonate (FEC, with a concentration of about 3 weight %), vinyl sulfate (DTD, with a concentration of about 0.3 weight %) and 1,3-propane sultone (1-3PS, with a concentration of about 0.3 weight %).

[0145] Positive electrode slurry stability test: The viscosity (25° C.) of the positive electrode slurry provided in each embodiment and comparative example at different times was tested using a viscosity tester. The test results are shown in Table 1.

[0146] Positive electrode sheet resistance test: The positive electrode sheets provided in each embodiment and comparative example were tested using a sheet resistance meter, model BER2500 (IEST Yuanneng Technology), electrode diameter 14 mm, applied pressure 20 MPa, duration 15 s, and the test results are shown in Table 1.

[0147] Battery DC internal resistance DCR test: Tested at 25°C on an electrochemical workstation battery test system, the battery capacity was adjusted to 50% SOC and left for 2 hours, the end-of-stay voltage U1 was recorded, discharged at a current of I(2C) for 10 seconds, and the end-of-discharge voltage U2 was recorded, DCR = (U1-U2) / I, the test results are shown in Table 1.

[0148] Battery high temperature cycle test:

[0149] The finished batteries prepared in Examples 1-8 and Comparative Examples 1-4 were subjected to 1C charge and 1C discharge cycle tests at 45°C with a charge and discharge voltage range of 1.5V-3.4V. The discharge capacity retention rate obtained after 2000 cycles is shown in Table 1.

[0150] Table 1

[0151]

[0152] Combined with the static viscosity data of the slurry in Table 1, it can be seen from Examples 1-8 and Comparative Examples 1-4 that the composite dispersant has an excellent dispersion effect, can significantly improve the stability of the positive electrode slurry, and the amount of the composite dispersant should not be too much or too little. Preferably, the mass of the composite dispersant accounts for 0.2%-1.0% of the total mass of the positive electrode active material, conductive agent, binder and composite dispersant.

[0153] Combining the electrode sheet resistance data and DCR DC resistance data in Table 1, it can be seen from Examples 1-8 and Comparative Examples 1-4 that the composite dispersant can make the dispersion effect of the positive electrode slurry more excellent, promote the uniform dispersion of the positive electrode particles, prevent particle agglomeration, and the conductive agent can be better dispersed on the surface of the positive electrode particles to form a uniform conductive network, thereby increasing the transmission rate of electrons, reducing the electrode sheet resistance and the DC internal resistance of the battery cell.

[0154] It can be seen from the high temperature cycle test data in Table 1 that after the sodium ion battery has been cycled for 2000 weeks, Example 1 has the highest cycle retention rate and the best cycle stability, which further proves that the polyacrylic acid maleic anhydride-bisphenol A polyoxyethylene ether composite dispersant has the best effect. In Example 2, a composite dispersant simply mechanically mixed with polyacrylic acid maleic anhydride and bisphenol A polyoxyethylene ether is used. Although the viscosity stability, resistance and cycle performance are reduced compared with Example 1, it still has significant advantages over Comparative Examples 3 and 4 in which a certain dispersant is used alone. It can achieve the best dispersion effect through the synergistic effect of the electrostatic repulsion mechanism and the steric hindrance mechanism, form a homogenized electrode structure, reduce structural failure and polarization growth during the cycle, and effectively improve the cycle performance of the sodium ion battery.

[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sodium ion battery positive electrode slurry, characterized in that: include: Positive electrode active material, conductive agent, binder, composite dispersant and solvent; The composite dispersant is a product formed by mechanically mixing an ionic dispersant with a polyoxyethylene ether nonionic dispersant, or a complex formed by chemically reacting an ionic dispersant with a polyoxyethylene ether nonionic dispersant, wherein the ionic dispersant is polyacrylic acid and its derivatives; The positive electrode active material is a polyanion material.

2. The positive electrode slurry for sodium ion battery according to claim 1, characterized in that: The mass of the composite dispersant accounts for 0.2%-1.0% of the total mass of the positive electrode active material, the conductive agent, the binder and the composite dispersant; And / or, the ionic dispersant is a copolymer formed by polyacrylic acid and other polycarboxylic acids or anhydrides; And / or, the polyoxyethylene ether nonionic dispersant is alcohol polyoxyethylene ether or phenol polyoxyethylene ether; and / or, in the composite formed after the chemical reaction between the ionic dispersant and the polyoxyethylene ether nonionic dispersant, the chemical reaction refers to an esterification reaction between the carboxyl group in the ionic dispersant and the hydroxyl group in the nonionic dispersant to form an ester bond; And / or, in the preparation of the composite dispersant, the mass ratio of the ionic dispersant to the polyoxyethylene ether nonionic dispersant is (1-2): (2-5); and / or, in the positive electrode slurry, the mass ratio of the positive electrode active material, the conductive agent, the binder and the composite dispersant is (93-97): (1-2): (1-4): (0.2-1.0), and the sum of the mass ratios is 100; And / or, the solid content of the positive electrode slurry is 55%-65%; And / or, the viscosity of the positive electrode slurry is 3000-12000 mPa·S.

3. The positive electrode slurry for sodium ion battery according to claim 2, characterized in that: The ionic dispersant is polyacrylic acid maleic anhydride or polyacrylic acid maleic acid; And / or, the polyoxyethylene ether nonionic dispersant is one or more of bisphenol A polyoxyethylene ether, glycerol polyoxyethylene ether, furan methanol polyoxyethylene ether, nonylphenol polyoxyethylene ether, and 1,2-propylene glycol polyoxypropylene polyoxyethylene ether; and / or, the positive electrode active material is selected from at least one of sodium ferric pyrophosphate, sodium ferrous sulfate, sodium vanadium phosphate, and sodium ferric phosphate; and / or, the conductive agent is selected from at least one of carbon black, graphene, carbon nanotubes or carbon nanofibers; And / or, the binder is selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene or PFA emulsion; and / or, the solvent is selected from at least one of N-methylpyrrolidone, ethanol, isopropanol or acetone; And / or, the composite dispersant is prepared according to the following method: deionized water is added to a mixture of an ionic dispersant and a polyoxyethylene ether non-ionic dispersant to form a gel solution, and then the mixture is stirred and reacted at 140-160° C. for 4-8 hours under vacuum conditions with a catalyst; and the reaction product is then post-treated to obtain the composite dispersant.

4. The positive electrode slurry for sodium ion battery according to claim 3, characterized in that: The composite dispersant is a composite formed by chemical reaction between polyacrylic acid maleic anhydride or polyacrylic acid maleic acid and bisphenol A polyoxyethylene ether.

5. The positive electrode slurry for sodium ion battery according to claim 4, characterized in that: The preparation method of the composite obtained by chemical reaction of polyacrylic acid maleic anhydride or polyacrylic acid maleic acid and bisphenol A polyoxyethylene ether comprises the following steps: S1: adding polyacrylic acid maleic anhydride or polyacrylic acid maleic acid and bisphenol A polyoxyethylene ether in a mass ratio of (1-2): (2-5) into a reaction kettle, and then adding deionized water to form a glue solution, stirring and reacting at 140-160° C. under vacuum conditions for 4-8 hours under the action of a catalyst; S2: After the reaction is completed, sodium carbonate solution is added to the reactor of step S1 and stirred, and then the solid product is washed with saturated brine, and then the washed solid product is dissolved in ethyl acetate, and finally the obtained liquid is vacuum dried to remove the ethyl acetate solvent, so as to obtain a composite.

6. The positive electrode slurry for sodium ion battery according to claim 5, characterized in that: The solid content of the glue is 8-12%; And / or, the vacuum condition is evacuated to 0.05-1.0Kpa; And / or, the catalyst is p-toluenesulfonic acid, and its addition amount accounts for 0.6-1% of the total mass of the two reaction raw materials; And / or, the mass concentration of the sodium carbonate solution is 8-12%, and the amount of the sodium carbonate added is such that the added sodium carbonate is 1 / 5 to 1 / 3 of the mass of the added catalyst; And / or, the stirring time in step S2 is 25-35 min.

7. A method for preparing a positive electrode slurry for a sodium ion battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: The binder, composite dispersant and solvent are mixed and stirred, and then a conductive agent is added for sizing, and then the positive electrode active material is added for homogenization, and then an appropriate amount of solvent is added to adjust the solid content and viscosity of the slurry to obtain a positive electrode slurry.

8. The preparation method according to claim 7, characterized in that: When the binder, composite dispersant and solvent are mixed and stirred, the amount of solvent added is controlled so that the solid content of the slurry reaches 5%-8%, and the stirring time is 120-180 minutes; The mixing time of the glue application is 90-150min; The homogenization time is 120-180 min.

9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode active layer coated on the surface of the current collector, wherein the positive electrode active layer is made of the positive electrode slurry according to claims 1-6 or made of the positive electrode slurry prepared by the preparation method of claims 7-8.

10. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Conductive agent dispersion liquid, electrode slurry, electrode, battery, and preparation methods thereof

    CN101752548A

  • Lithium ion battery positive electrode slurry, preparation method thereof and lithium ion battery

    CN110797536A

  • Preparation method of positive electrode slurry, positive electrode plate and lithium ion battery

    CN114284465A

  • Binder composition, sodium ion battery positive electrode slurry and sodium ion battery

    CN116111091A

  • Positive plate and preparation method thereof, energy storage equipment and electric equipment

    CN116504985A

Cited By

  • Positive electrode slurry and sodium ion battery

    CN120376646A

  • Raw material composition of positive electrode material, positive electrode material, preparation method of positive electrode material, pole piece and battery

    CN122436492A

  • Raw material composition of positive electrode material, positive electrode material, preparation method thereof, electrode sheet and battery

    CN122436492B